Transradial Approach to Coronary Interventions in Central Nepal - Laudari, Shankar; Gurung, Puran; Gurung, Kushal; Dhakal, Abiona; Upadhyay, Hari Prasad (Journal of National Heart and Lung Society Nepal, 2023)
Background The transradial approach (TRA) has gained popularity worldwide and it is the preferred access in many cardiac centers in Nepal. The aim of this study is to document single operator experience with TRA and its complications. Results A total of 214 patients were included with 114(53.27%) males and 100(46.73%) females. The mean age was (62.51 ± 12.47) years. The total transradial success rate was 88.78% for Coronary interventions. The crossover rate from radial to femoral access was 11.22%. The primary causes for crossover were severe tortuosity of the aorta and brachiocephalic trunk, radial artery spasm, puncture failure, and radial loop. Conclusions TRA is safe and can be applied in the majority of cases. The routine assessment of dual hand circulation before TRA might not be necessary.